2010
DOI: 10.1371/journal.ppat.1001010
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli Modulates Immune Responses and Its Curli Fimbriae Interact with the Antimicrobial Peptide LL-37

Abstract: Bacterial growth in multicellular communities, or biofilms, offers many potential advantages over single-cell growth, including resistance to antimicrobial factors. Here we describe the interaction between the biofilm-promoting components curli fimbriae and cellulose of uropathogenic E. coli and the endogenous antimicrobial defense in the urinary tract. We also demonstrate the impact of this interplay on the pathogenesis of urinary tract infections. Our results suggest that curli and cellulose exhibit differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
223
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(244 citation statements)
references
References 64 publications
9
223
0
6
Order By: Relevance
“…In the present study, in-vitro biofilm production was recorded in 76.5% of UPEC isolates; this is in contrast to other studies that showed different percentages of biofilm production among UPEC with 63.6%, 60.15%, and 51.9 % recorded in Egypt, India, and Nepal, respectively (15,40,41). Curli production was detected in 45.7% of the tested UPEC clinical isolates; a similar study from Sweden reported the detection of curli production among 54% of UPEC (42). A significant correlation was found between biofilm production and MDR phenotype among UPEC in the current study.…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, in-vitro biofilm production was recorded in 76.5% of UPEC isolates; this is in contrast to other studies that showed different percentages of biofilm production among UPEC with 63.6%, 60.15%, and 51.9 % recorded in Egypt, India, and Nepal, respectively (15,40,41). Curli production was detected in 45.7% of the tested UPEC clinical isolates; a similar study from Sweden reported the detection of curli production among 54% of UPEC (42). A significant correlation was found between biofilm production and MDR phenotype among UPEC in the current study.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that curli fibers produce an immune response by activating the host coagulation system and thus promoting an influx of white blood cells (34). However, curli fimbriae can also promote resistance to the host antimicrobial peptide LL-37 (36). Additional mutations in the yfiR deletion strain were therefore made to determine if the increased expression of curli fimbriae, or possibly even the increase in cellulose production, could be responsible for the attenuation of the yfiR deletion strain in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have demonstrated the ability of curli fimbriae to induce an immune response through Toll-like receptor 2 (TLR2) activation and generation of proinflammatory fibrinopeptides and by activating inducible nitric oxide synthase, a defense mechanism that produces large amounts of nitric oxide (33)(34)(35). Increased bacterial resistance to the antimicrobial peptide LL-37 in curli-fimbriated E. coli has also been demonstrated (36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A csgA mutant or csgB/csgG double mutant are both attenuated during acute infection in a murine model of cystitis, suggesting that curli fibers contribute to UTI pathogenesis (126). This defect in virulence could be partially explained by the binding of curli fibers with the human antimicrobial peptide LL-37 and the murine ortholog, cathelicidinrelated antimicrobial peptide (CRAMP) (127). This interaction is believed to sequester these peptides and attenuate their antimicrobial activity.…”
Section: Role Of Curli In Biofilm Formation and Upec Pathogenesismentioning
confidence: 99%